Tensile Behavior of Acrylonitrile Butadiene Styrene at Different Temperatures. (4th April 2020) - Li, Jiquan; Jia, Yadong; Li, Taidong; Zhu, Zhou; Zhou, Hangchao; Peng, Xiang; Jiang, Shaofei
Abstract : Temperature greatly influences the mechanical response of acrylonitrile butadiene styrene (ABS). The tensile behavior of ABS was explored in this study. The tensile experiments were conducted at a wide range of temperatures (from 40 ° C to 130 ° C). A model was established to reveal the quantitative relationship between temperature and tensile behavior of ABS. The results of tensile experiments showed that tensile behavior of ABS exhibited glassy state and high-elastics state. The model was also divided into two parts that rely on the boundary of glass transition temperature, in which the parameters of the model were calculated by the fitting method. The model predictions showed a good agreement with the results of the experimental tensile test. This study provides the quantitative relationship between temperature and tensile behavior of ABS, which saves time and experimental costs.